2018
DOI: 10.1371/journal.pone.0206712
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance is lower in Staphylococcus aureus isolated from antibiotic-free raw meat as compared to conventional raw meat

Abstract: The frequent use of antibiotics contributes to antibiotic resistance in bacteria, resulting in an increase in infections that are difficult to treat. Livestock are commonly administered antibiotics in their feed, but there is current interest in raising animals that are only administered antibiotics during active infections. Staphylococcus aureus (SA) is a common pathogen of both humans and livestock raised for human consumption. SA has achieved high levels of antibiotic resistance, but the origins and locatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…In all, 33 studies restricted use of antibiotics for all non-therapeutic purposes,48 96–127 and 19 restricted antibiotic growth promoters only 128–146. A total of 21 studies were classified into the ‘other/undetermined’ category 52 53 83 100 137 147–162. Of note, seven studies consisted of two different interventions and were therefore included into two separate categories 48 52 53 83 100 122 137…”
Section: Resultsmentioning
confidence: 99%
“…In all, 33 studies restricted use of antibiotics for all non-therapeutic purposes,48 96–127 and 19 restricted antibiotic growth promoters only 128–146. A total of 21 studies were classified into the ‘other/undetermined’ category 52 53 83 100 137 147–162. Of note, seven studies consisted of two different interventions and were therefore included into two separate categories 48 52 53 83 100 122 137…”
Section: Resultsmentioning
confidence: 99%
“…A similar research conducted in Egypt revealed 78% of S. aureus isolates showed resistance to vancomycin and erythromycin, and 100% of the strains showed resistance to gentamycin (Osman et al, 2016). There are many studies in which S. aureus antibiotic-resistant strains have been identified in different food products (Hanson et al, 2011;Basanisi et al, 2017;Rong et al, 2017;Haskell et al, 2018;Pekana and Green, 2018;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…In poultry rearing, excessive antibiotics are commonly used for disease prevention and growth promotion, leading to the occurrence of antibiotic-resistant bacteria ( Krishnasamy et al, 2015 ; Haskell et al, 2018 ). A considerable increase in multidrug-resistant (MDR) Salmonella has been observed, and the number of MDR Salmonella infections has increased worldwide over the past few years ( Fardsanei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%